DIVERSITY OF MYOFIBROUS CONSTITUTION WITHIN A MUSCLE - UETAKE, Teruo (Journal of The Showa Medical Association, 1989)
The myofibrous constitution of three cross-sectional regions (proximal, medial and distal) of the muscle, m. quadriceps femoris, and the hamstrings of the crab-eating macaque were compared to determine if there is myofibrous diversity within a muscle. Two adult female crab-eating macaques were fixed with 10 % formalin. After a slice of muscle was dyed using Sudan Black B for microscopic examination, the type (white, intermediate or red) and area of the muscle fiber were examined. The total number of muscle fibers in a defined re-gion was also determined. The results were summarized as follows : 1) The proportion of white fiber type (40-70 %) was highest of the three in all sectional regions of the m. quadriceps femoris and the hamstrings. However, the proportion of the other two types differed from muscle to muscle, and from subject to subject. 2) In the m. quadriceps femoris, especially in the m. vastus lateralis, m, vastus medialis and m. rectus femoris, the proportion of white fiber was higher in the distal than in the proximal region, and the proportion of red fiber was higher in the proximal than in the distal region. 3) In the hamstrings, especially in the m. biceps femoris and m. semimembranosus proprius, the proportion of white fiber was higher in the proximal than in the distal region, and the proportion of red fiber was higer in the distal than in the proximal region. 4) In semimembranosus accesorius, however, the proportions of the three muscle fiber types were similar to those in the m. quadriceps femoris. 5) The area of each muscle fiber type in hamstring was larger than that in m. quadriceps femoris in the following order : m. semitendinosus> m. biceps femoris> m. semimembranosus accesorius> m. semimembranosus proprius> m. vastus lateralis> m, rectus femoris> m. vastus medialis> m. vastus intermedius. Also, the area of each muscle fiber type was generally larger in the prox-imal than in the distal region. The results suggested myofibrous diversity that provides intra-muscular differentiation of two muscle groups.